2016
DOI: 10.1158/1940-6207.capr-15-0107
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Adipose Tissue-Derived Lysophospholipids Promote Estrogen Receptor–Negative Mammary Epithelial Cell Proliferation

Abstract: Lysophosphatidic acid (LPA), acting in an autocrine or paracrine fashion through G protein-coupled receptors, has been implicated in many physiological and pathological processes including cancer. LPA is converted to lysophosphatidylcholine (LPC) by the secreted phospholipase, autotaxin (ATX). Although various cell types can produce ATX, adipocyte-derived ATX is believed to be the major source of circulating ATX and also to be the major regulator of plasma LPA. In addition to ATX, adipocytes secrete numerous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 57 publications
6
31
0
Order By: Relevance
“…The resulting LPA is then able to activate LPA receptor-mediated signaling in the tumor cells. This bi-directional signaling between adipose tissue and breast tumors has been confirmed by other investigators [34,35]. Indeed, adipocytes produce~40% of the body's ATX [36,37] and the breast is rich in adipose tissue.We subsequently showed that exposing cultured human breast adipose tissue to γ-radiation increased the secretion of ATX as well the expression of LPA 1 and LPA 2 receptors downstream of DNA damage [21].…”
supporting
confidence: 68%
“…The resulting LPA is then able to activate LPA receptor-mediated signaling in the tumor cells. This bi-directional signaling between adipose tissue and breast tumors has been confirmed by other investigators [34,35]. Indeed, adipocytes produce~40% of the body's ATX [36,37] and the breast is rich in adipose tissue.We subsequently showed that exposing cultured human breast adipose tissue to γ-radiation increased the secretion of ATX as well the expression of LPA 1 and LPA 2 receptors downstream of DNA damage [21].…”
supporting
confidence: 68%
“…This amplifies the inflammatory cycle and promotes accumulation of inflammatory leukocytes in the inflamed adipose tissue [30,32]. Bi-directional signaling between breast tumors and surrounding adipose tissue through the ATX-LPA-inflammatory cycle ( Figure 3) has been confirmed [81,82]. At the organism level, we showed this increased ATX activity is measurable in the plasma of mice with advanced breast cancer [29].…”
Section: Maladaptive Effects Of Excessive Atx Secretion and Lpa Signamentioning
confidence: 51%
“…Lysophosphatidic acid (LPA; monoacyl-glycerol-3-phosphate) serves as a mitogen and a stimulator of motility in many cell types [ 24 ], acting in either an autocrine or paracrine fashion via G protein-coupled receptors. LPA is involved in many physiological and pathological processes, including cancer [ 25 ]. LPA enhances tumor growth, metastasis, and chemoresistance [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPA is derived from lysophosphatidylcholine (LPC) via the action of a secreted phospholipase termed autotaxin (ATX), which was originally identified as an “autocrine motility factor” of tumor cells [ 24 ]. As ATX promotes both tumor formation and angiogenesis [ 24 ], and as ATX levels are elevated in several human malignancies [ 24 , 27 ], many researchers believe that ATX may be a promising therapeutic target in patients with chronic inflammation and cancer [ 25 , 26 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%